A Sustainable Reuse of Agro-Industrial Wastes into Green Cement Bricks - Chin, Wei Quan; Lee, Yeong Huei; Mugahed, Amran; Roman, Fediuk; Nikolai, Vatin; Ahmad Kueh, Beng Hong; Lee, Yee Yong (MDPI, 2022)
The fabrication of bricks commonly consumes relatively high natural resources. To reduce the carbon footprint in the brick production industry, repurposing industrial wastes in the making of sustainable bricks is a recent trend in research and application. Local wastes, such as oil palm shell (OPS), palm oil fuel ash (POFA), and quarry dust (QD), are massively produced annually in the palm oil-exporting countries. Moreover, QD from mining industries is hazardous to both water and air quality. For better waste management in marching towards sustainability, these wastes should be given their second life as construction materials. Therefore, this paper investigates the possibility of incorporating agro-industrial wastes into the brick mixture by examining their properties by means of several standardized tests. For the mix design, a 100% replacement of coarse aggregate with OPS, 20% replacement of cement with POFA, 20% cement weight of limestone as admixture, and 0 to 50% replacements of fine aggregate with QD are experimentally considered. The optimum mix of these wastes is preliminarily determined by focusing on high compressive strength as an indicator. Other examinations include splitting tensile, flexural strength, water absorption, and efflorescence tests. Although the agro-industrial waste cement brick is 18% lower in the strength to weight ratio compared to that of conventional, it is observed that it has better late strength development due to its POFA pozzolanic properties. Moreover, the proposed green cement brick is further checked for compliance with several standards for feasible use in the construction industry. Financially, the cost for the brick with the new mix design is almost equivalent to that of conventional. Hence, this green cement brick is reasonable to be employed in the construction industry to promote material sustainability for better waste management.